2013
DOI: 10.1007/s11738-013-1244-7
|View full text |Cite
|
Sign up to set email alerts
|

Hairy roots of Dracocephalum moldavica: rosmarinic acid content and antioxidant potential

Abstract: Hairy roots of Dracocephalum moldavica L. were induced using Agrobacterium rhizogenes strain A4. Transformed roots were obtained from shoot explants with low transformation frequency of up to 3 %. The effects of different liquid media: Murashige and Skoog (MS), Gamborg et al. (B5) and Woody Plant (WP) with full-and half-strength ( MS, B5, WP), on biomass accumulation and rosmarinic acid (RA) content were investigated. The hairy roots were cultured in photoperiod (16 h light/8 h dark) and darkness. Biomass of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 34 publications
3
33
0
Order By: Relevance
“…3a, b). Similar results have demonstrated that TPC and TFC were higher in hairy roots compared to non-transgenic roots in Dracocephalum moldavica (Weremczuk-Jezyna et al, 2013) and P. multiflorum (Thiruvengadam et al, 2014a).…”
Section: Comparison Of Total Phenolics and Flavonoids Content (Tpc Ansupporting
confidence: 85%
“…3a, b). Similar results have demonstrated that TPC and TFC were higher in hairy roots compared to non-transgenic roots in Dracocephalum moldavica (Weremczuk-Jezyna et al, 2013) and P. multiflorum (Thiruvengadam et al, 2014a).…”
Section: Comparison Of Total Phenolics and Flavonoids Content (Tpc Ansupporting
confidence: 85%
“…Consistently, hairy roots were exhibited of higher antioxidant activity in D. moldavica (Weremczuk-Jezyna et al, 2013), P. multiflorum (Thiruvengadam et al, 2014a), M. charantia (Thiruvengadam et al, 2014b), and Isatis tinctoria (Gai et al, 2015). Means ± standard deviation of three replicates (n = 3) within a column a-d , or row x-z followed by the same letters are not significantly different according Duncan's multiple range test at P ≤ 0.05.…”
Section: Comparison Of Antioxidant Activity In Transgenic Hairy Rootsmentioning
confidence: 69%
“…The total phenolic content of hairy roots was 21.51 mg/g GAE and their total flavonoid content was 2.75 mg/g QE; total phenolic content of non-transgenic roots was 15.10 mg/g GAE and their total flavonoid content was 1.91 mg/g QE. Similarly, total phenolic and flavonoid contents were higher in hairy roots compared to non-transgenic roots of Dracocephalum moldavica (Weremczuk-Jezyna et al, 2013), P. multiflorum (Thiruvengadam et al, 2014a) and M. charantia (Thiruvengadam et al, 2014b).…”
Section: Comparison Of Total Phenolic and Flavonoid Contents (Tpc Andmentioning
confidence: 90%
“…In Agastache foeniculum hairy root cultures, a fourfold increase in RA content was observed . The production of RA was elevated threefold in D. moldavicac hairy root culture . Reports showed high methoxylated flavonoid content in the Labiatae family.…”
Section: Introductionmentioning
confidence: 95%